PENGARUH SIKAP KEWIRAUSAHAAN, MOTIVASI, DAN INOVASI PRODUK TERHADAP KEBERHASILAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) KECAMATAN CIBUNGBULANG - Gustamam, Ripal; Samsuri; Ismartaya (Karimah Tauhid, 2023)
The greater the unemployment and poverty rates in Indonesia, opening a UMKM business is one of the solutions to reduce the soaring numbers. UMKM or Micro, Small and Medium Enterprises are productive businesses owned by individuals who stand alone and are not subsidiaries or branches of the company, therefore Human Resource management is very necessary for the success of UMKM businesses. This study aims to determine the effect of entrepreneurial attitudes, motivation and product innovation partially on the success of UMKM businesses in Cibungbulang District. The method used in this research is a quantitative approach. The samples used amounted to 50 samples with saturated sampling techniques. The data analysis technique in this study uses Multiple Linear Regression Analysis.